Structural and functional properties of Antarctic fish cytoglobins-1: Cold-reactivity in multi-ligand reactions - Giordano, Daniela; Pesce, Alessandra; Vermeylen, Stijn; Abbruzzetti, Stefania; Nardini, Marco; Marchesani, Francesco; Berghmans, Herald; Seira, Constantí; Bruno, Stefano; Javier Luque, F; di Prisco, Guido; Ascenzi, Paolo; et al. (Computational and Structural Biotechnology Journal, 2020)
While the functions of the recently discovered cytoglobin, ubiquitously expressed in vertebrate tissues, remain uncertain, Antarctic fish provide unparalleled models to study novel protein traits that may arise from cold adaptation. We report here the spectral, ligand-binding and enzymatic properties (peroxynitrite isomerization, nitrite-reductase activity) of cytoglobin-1 from two Antarctic fish, Chaenocephalus aceratus and Dissostichus mawsoni, and present the crystal structure of D. mawsoni cytoglobin-1. The Antarctic cytoglobins-1 display high O2 affinity, scarcely compatible with an O2-supply role, a slow rate constant for nitrite-reductase activity, and do not catalyze peroxynitrite isomerization. Compared with mesophilic orthologues, the cold-adapted cytoglobins favor binding of exogenous ligands to the hexa-coordinated bis-histidyl species, a trait related to their higher rate constant for distal-His/heme-Fe dissociation relative to human cytoglobin. At the light of a remarkable 3D-structure conservation, the observed differences in ligand-binding kinetics may reflect Antarctic fish cytoglobin-1 specific features in the dynamics of the heme distal region and of protein matrix cavities, suggesting adaptation to functional requirements posed by the cold environment. Taken together, the biochemical and biophysical data presented suggest that in Antarctic fish, as in humans, cytoglobin-1 unlikely plays a role in O2 transport, rather it may be involved in processes such as NO detoxification.